Witchcraft and occult crime within a contemporary Canadian context. - McDonald, Tracesandra Jade. (University of Ottawa (Canada), 1999)
This thesis deals with the place of witchcraft and occult crime within contemporary social relations, particularly in the areas of law and enforcement. The methodology combines a sampling of case law for charges laid under section 365 of the Canadian Criminal Code, outlining the crime of 'Pretending to Practise Witchcraft', as well as the surveying of a decade of Canadian media coverage, between the years of 1987 and 1997, for events associated with witchcraft and the occult. Coverage was studied for the selection of events that invoked either formal intervention by the state or some manner of informal community mobilization. The analysis is two-fold. The case law for section 365 is examined in depth to determine how the law has interpreted the crime of witchcraft over this past century. Ten cases are reviewed to determine how the court system defined and tried the crime of witchcraft as well as to identify any major shifts or changes in this process. In the second component of the thesis, dealing with events identified through media coverage, Jock Young's ' Square of Crime' is used as framework for the analysis and organization of the data. (Abstract shortened by UMI.)
Keywords: Religion, General.